Comparison and Optimization of DNA Extraction Methods from Cervical Cells Collected in ThinPrep® PreservCyt - Silva, Andreia; Salta, S; Henrique, R; Jerónimo, C (Citotech Online - Case Review, 2020)
Cervical cancer is the ninth leading cancer in women in Portugal. Cervical cancer screening methods have changed since the implementation of the cytology-based test developed by George Papanicolaou until the human papillomavirus-based screening. Nowadays, new biomarkers like deoxyribonucleic acid (DNA) methylation has been proposed as potential triage method of samples testing positive for human papillomavirus The aim of this study was to optimize and compare three different DNA extraction methods for further methylation analysis. DNA from sixteen cervical samples collected in ThinPrep® PreservCyt was extracted by the phenol-chloroform method, by QIAamp® MinElute™ Media kit (QIAGEN, Hilden) and by Blood DNA Isolation Mini Kit (Norgen Biotek, Ontario). After quantification, DNA was modified by Sodium Bisulfite and amplified by Quantitative Specific Methylation Polymerase Chain Reaction for β- Actin gene. Finally, Cycle threshold (Ct) mean values were evaluated. The phenol-chloroform method had the higher sample input and, consequently allowed for a higher DNA quantity. Fifteen mL of sample allowed for get 13500ng with the phenol-chloroform method meanwhile 2mL of sample provided 8940ng with QIAamp® MinElute™ Media kit and 927ng with Blood DNA Isolation Mini Kit. However, commercial kits presented higher efficiency and advantages as being less time consuming and easier to perform. No significant differences were observed for amplification Ct values between the three DNA extraction methods neither between samples archived for ten or fourteen months. Concluding, the three methods provided DNA to amplification but the optimization of commercial kits turned out to be more advantageous.